Decreased levels of alpha-1-acid glycoprotein are related to the mortality of septic patients in the emergency department (Clinics, 2013)
OBJECTIVE: To determine the validity of alpha-1-acid glycoprotein as a novel biomarker for mortality in patients with severe sepsis. METHODS: We prospectively included patients with severe sepsis or septic shock at the emergency department at a single tertiary referral teaching hospital. All of the patients were enrolled within the first 24 hours of emergency department admission, and clinical data and blood samples were obtained. As the primary outcome, we investigated the association of serum levels of alpha-1-acid glycoprotein and 96-hour mortality with logistic regression analysis and generalized estimating equations adjusted for age, sex, shock status and Acute Physiology and Chronic Health Evaluation II score. RESULTS: Patients with septic shock had lower alpha-1-acid glycoprotein levels at the time of emergency department admission compared to patients without shock (respectively, 149.1 ±42.7 vs. 189.8 ±68.6; p = 0.005). Similarly, non-survivors in the first 96 hours were also characterized by lower levels of alpha-1-acid glycoprotein at the time of emergency department admission compared to survivors (respectively, 132.18 ±50.2 vs. 179.8 ±61.4; p = 0.01). In an adjusted analysis, alpha-1-acid glycoprotein levels ≤120 mg/dL were significantly associated with 96-hour mortality (odds ratio = 14.37; 95% confidence interval = 1.58 to 130.21). CONCLUSION: Septic shock patients exhibited lower circulating alpha-1-acid glycoprotein levels than patients without shock. Alpha-1-acid glycoprotein levels were independently associated with 96-hour mortality in individuals with severe sepsis.